2017
DOI: 10.1002/pi.5482
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of micelles from poly(butylene succinate) and poly(2‐methacryloyloxyethyl phosphorylcholine) copolymers as a potential drug carrier

Abstract: A series of copolymers of poly(2‐methacryloyloxyethyl phosphorylcholine)‐b‐poly(butylene succinate)‐b‐poly(2‐methacryloyloxyethyl phosphorylcholine) (PMPC‐b‐PBS‐b‐PMPC) were synthesized by atom transfer radical polymerization. The structure of the polymers was characterized by 1H NMR and infrared spectroscopy, and their thermal properties were described using TGA and DSC. In aqueous solutions, the PMPC‐b‐PBS‐b‐PMPC could form micelles with sizes ranging from 108 to 170 nm. In vitro release studies showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…P­(MPC- co -MaPCL) and FA-P­(MPC- co -MaPCL) micelles were prepared by a combination of solvent evaporation and dialysis methods according to our previous reports. ,, Briefly, 10 mg of copolymer P­(MPC- co -MaPCL) or FA-P­(MPC- co -MaPCL) was dissolved fully in 3 mL of mixed solution of CHCl 3 and CH 3 OH (v:v = 3:1) and the solution was added dropwise into 10 mL of deionized water under vigorous stirring. The resulting suspension was stirred overnight and dialyzed for 12 h to form micelles.…”
Section: Methodsmentioning
confidence: 99%
“…P­(MPC- co -MaPCL) and FA-P­(MPC- co -MaPCL) micelles were prepared by a combination of solvent evaporation and dialysis methods according to our previous reports. ,, Briefly, 10 mg of copolymer P­(MPC- co -MaPCL) or FA-P­(MPC- co -MaPCL) was dissolved fully in 3 mL of mixed solution of CHCl 3 and CH 3 OH (v:v = 3:1) and the solution was added dropwise into 10 mL of deionized water under vigorous stirring. The resulting suspension was stirred overnight and dialyzed for 12 h to form micelles.…”
Section: Methodsmentioning
confidence: 99%
“…These methods required the use of complicated multi‐step synthesis, long reaction times and toxic metal catalysts to some extent. Another method for the improvement of PBS is the introduction of functional hydrophilic polymers . Recently, we prepared a series copolymers of poly(2‐methacryloyloxyethyl phosphorylcholine)‐ block ‐PBS‐ block ‐poly(2‐methacryloyloxyethyl phosphorylcholine) (PMPC‐ b ‐PBS‐ b ‐PMPC) by atom transfer radical polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…Another method for the improvement of PBS is the introduction of functional hydrophilic polymers . Recently, we prepared a series copolymers of poly(2‐methacryloyloxyethyl phosphorylcholine)‐ block ‐PBS‐ block ‐poly(2‐methacryloyloxyethyl phosphorylcholine) (PMPC‐ b ‐PBS‐ b ‐PMPC) by atom transfer radical polymerization . The results showed that these copolymers could form nano‐sized micelles in water with phosphorylcholine shell and PBS core structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copolymer of PCL- b -PMPC was synthesized in three steps. First, hydroxyl-terminated poly­(ε-caprolactone), PCL-OH, was synthesized by ring-opening polymerization (ROP) with benzyl alcohol as the initiator and Sn­(Oct) 2 as the catalyst. , Then bromoisobutyryl-terminated poly­(ε-caprolactone), PCL- i BuBr, was synthesized through a reaction of PCL-OH and 2-bromoisobutyryl bromide using TEA as the catalyst in a solvent of CH 2 Cl 2 . , Afterward, copolymer PCL- b -PMPC was synthesized via ATRP in the presence of CuBr and bpy, using THF and CH 3 OH as a mixed solvent at 50 °C for 36 h. PCL- b -PMPC was purified by dialysis using a dialysis bag with MWCO-3500 Da for 3 days in water. Finally, PCL- b -PMPC was collected after lyophilization (yield 84%) and then characterized by 1 H NMR spectroscopy.…”
Section: Methodsmentioning
confidence: 99%